Women's work, health and empowerment - Gandhi, Anjali; Jamia Millia Islami (India) : Dept. of Social work; Jamia Millia Islami (India) : Sarojini Naidu Centre for Women's Studies; Seminar on "National Policy of Empowrment of Women" (2002: Sarojini Naidu Centre for Women's Studies) (Delhi : Aakar, 2006)
Contributed articles on women issues in India' also includes a brief report on the seminar
" This book is the result of recommendations of the Seminar on "National Policy of Empowerment of Women" jointly organized by Sarojini Naidu Centre for Women's Studies and the Department of Social Work, Jamia Millia Islamia, New Delhi" - verso of t.p.
Includes bibliographical references and index
Keywords: Feminism -- India -- Congresses; Women in development -- India -- Congresses; Women -- Health and hygiene -- India -- Congresses